General Education Teachers’ Awareness Of The Requirements Of Full Inclusion For Students With Disabilities - Dareen Khlaifat (Migration Letters, 2024)
The aim of this study is to identify the awareness degree of male and female teachers of general education of the full inclusion requirements. The descriptive approach that based on describing the general education teachers’ awareness of the requirements of full inclusion for students with disabilities at public school setting was adopted. An electronic questionnaire was specifically prepared to achieve the aim of this study and sent to the study subjects via an electronic link. The study sample consisted of 153 males and 367 females (N=520) of general education teachers at the Eastern Province in kingdom of Saudi Arabia, in light of a number of the study variables. The results indicated that the teachers have a high level of awareness in terms of the teaching adaptation requirements, followed by awareness of the environmental modification requirements, educational requirements, awareness requirements, and support requirements. The results also revealed that there are significant differences at the level of (α ≤ 0.05) in the domains of the inclusion requirements that are attributed to the gender variable in favor of female teachers, and in the domains of awareness o[1]f the inclusion requirements that are attributed to the variable of educational qualification between (diploma and bachelor’s degree holders) in favor of the Bachelor’s degree holders, between (diploma and postgraduate studies ) in favor of postgraduate studies and between postgraduates and bachelor’s degree holders in favor of the Bachelor’s degree holders. The results of the awareness of the inclusion requirements among those with the experience of (5-10 years and 16 or more) and those with (11-15 and 16 or more) indicated that there are significant differences at the level of (α ≤ 0.05) in favor of (16 or more) years of experience. Finally, the results revealed that there are differences in the degree of teachers’ awareness of the requirements of full inclusion that are attributed to the variable of whether teachers have relatives with disabilities or not in favor of having relatives with disabilities.